Effect of pyrolysis temperature and thermal conditioning on the coke-forming potential of bio-oils - Melisa Bertero (2011)
Bio-oil from the pyrolysis of pine sawdust was subjected to a thermal conditioning process aimed at inducing changes in its composition and physicochemical properties. The objective was to facilitate the coprocessing of bio-oil together with conventional feedstocks in catalytic cracking of hydrocarbons (FCC). The pyrolysis was performed at different conditions (heating ramp 15 °C/min, final temperatures from 300 to 650 °C), yielding varying proportions of gases, tar, char, and bio-oil. The maximum bio-oil yield (43.7 wt %) was obtained at 550 °C. Bio-oil showed a high concentration of oxygenated compounds (about 48 wt %) including acids, esthers, aldehydes, ketones, furans, alcohols, sugars, phenols, and ethers, together with hydrocarbons and close to 50 wt % of water. The thermal treatments included different conditions (final temperatures from 350 to 550 °C and heating ramps from 8 to 12 °C/min), and the most important consequences were that the concentrations of compounds believed to be coke precursors, such as phenols decreasesd significantly (between 30 and 50% and particularly some phenolic ethers, up to 90%), and high molecular weight compounds (between 50 and 65%). Some physicochemical properties in the bio-oil changed positively, the CCR decreasing from 4.8 wt % to about 1.5 wt %, and the effective hydrogen index increasing by 30%. Most of the carbon and the hydrogen remained in the liquid phase after the thermal treatment, while about 40% of the oxygen was removed. The byproduct in the thermal process (tar, gases, and pyrolytic lignin), represented an overall yield of about 5 wt %, and the overall yield of conditioned liquid was 38.7 wt % based on the sawdust raw material.